Metodologia de gerenciamento do processo de serviços em micro e pequenas empresas da região central do Rio Grande do Sul - BR - Tronco, Catia Regina (2006)
The present study presents a model to management process of services in micro and small companies - MPEs, of the central area of Rio Grande do Sul. MPEs, object of this study, were in number of forty three (43) active companies in section services,that were part of the Program of Business Extension, in the period understood between 2004 and 2005. For the accomplishment of the research, it was used data collected by technical consultants of the business extension, which data were obtained through interviews with entrepreneurs and logged in a checklist. After, they were analyzed through statistics programs, when there was the crossing data, in order to have a perfected analysis, and finally the presentation of the proposed model, that for its simplicity, it is only destined to MPEs. The data analysis took to the conclusion that most of MPEs that render services don't elaborate plans in order to develop new services or looking for to reach new customers, and due to that they stagnate in the market, coming, later, dying. It was noticed that most of MPEs don't possess procedures and operational instructions for services execution, what turns more challenging the establishment of patterns in the offered services. Finally, MPEs demonstrate real need of a more efficient control in what concerns development and execution of the rendered services, in a way to guarantee the maintenance, recruiting of new services and execute services intending to satisfy customer's demands.